RHETORICAL ONTOLOGY AND THEO-AESTHETICS BY DAVID BENTLEY HART - Lozovytskyi , Vasyl (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The work investigated the rhetorical ontology and theological aesthetics of D. B. Hart. Hart advocates for overcoming the "Neopalamite synthesis", which prevailed in the Orthodox theology of the 20th century, and criticizes neopatristics as a contemporary Orthodox project. The acceptance of the unity of the Christian tradition of the West and the East in the theology of D. Hart is due to his openness to the "Radical Orthodoxy" of John Milbank. The aim is to investigate the evolution of D. B. Hart’s theology, to critically analyse its main ideas, and to identify probable lines of influence on Ukrainian theology. Research methods are based on generally accepted philosophical and theological tools. Research results. Christian rhetoric has as its basis the assertion that in God himself the truth of distinction is most fully and perfectly expressed, which is not a gap, but is an infinite expression within the very infinity of God. An important source of D. Hart’s theology is the theory of the "analogy of being", which is based not on the relationship between the Creator and creation, but on the Trinitarian life itself. In the theology of D. Hart, in such a Trinitarian ontology, the postmodern "tragedy of distinction" is an impassable distance of absence, impenetrability of violence. All the "existence" of a contingent being has no ground for Harth, except the generous and unnecessary gift of the extension of one’s own Beauty and Goodness by the Triune God. Because God is a relationship of Love, and similarly, all created things exist in relation to individuals who are in a relationship of love with each other, with God, and concerning the world. Discussion. In contrast to Heidegger, Christian theology, for the first time in the history of Western metaphysics, asserted with full confidence the ontological distinction between Being and being. If for M. Heidegger the being always falls into an impassable distance, then for D. Hart, following Gregory of Nyssa, creation has the capacity for infinite ascension to God. Conclusions. The American Orthodox theologian goes beyond the thematic boundaries of Orthodox theology and works in a broader general Christian context. Moreover, in Hart’s project, which follows the guidelines of Radical Orthodoxy, theology enters the contemporary philosophical landscape as an independent subject that not only perceives the "languages of the world" but consistently and uncompromisingly puts forward its own narrative. In its openness, which is nevertheless polemical and not conducive to the "dissolution" of theology in philosophical meta-narratives, Hart’s theology takes Orthodox thought to another level, which overcomes the limitations and catastrophic flaws of the neo-patristic synthesis, which becomes a vivid testimony to the transition of Orthodox theology to a state of "post-neo-patristic".